KEKERASAN BERBASIS GENDER : BELENGGU PATRIARKI TERHADAP PEREMPUAN DALAM NOVEL TEMPURUNG KARYA OKA RUSMINI - Zahratul Umniyyah (Pusat Studi Gender Universitas Jember, 2021)
Violence against women still often occurs in societies adhering to a patriarchal system. The patriarchal system gives many disadvantages to women whose rights are shackled. The purpose of this study is to describe the lives of female figures who are victims of physical and psychological violence due to men and women who adhere to a patriarchal system. The results of this study indicate that violence against women is committed by both men and women. This violence has deeply traumatized female figures.